Revealing the effect of structural components made of sandwich panels on loading the container transported by railroad - Vatulia, Glib; Lovska, Alyona; Myamlin, Sergiy; Stanovska, Iraida; Holofieieva, Maryna; Horobets, Volodymyr; Nerubatskyi, Volodymyr; Krasnokutskyi, Yevhen (Eastern-European Journal of Enterprise Technologies, 2023)
The object of this study is the processes of emergence, perception, and redistribution of loads in the supporting structure of a 1CC size container with end walls made of sandwich panels. To reduce the longitudinal load of the container under operational modes, the introduction of sandwich panels into its design is proposed. This solution is implemented on the example of its end walls as the most loaded component of the body in operation. The thickness of the sandwich panel sheet was determined, provided that the strength in operation is ensured. Mathematical modeling of dynamic load of a container with end walls made of sandwich panels placed on a platform car during shunting co-impact was carried out. It was established that taking into account the proposed improvement makes it possible to reduce the dynamic loads that the container perceives by 10 % compared to the typical structure. The results were confirmed by computer simulation of the dynamic load of the container. The models formed within the framework of the study were verified according to the F-criterion. The results of calculations for the strength of the container showed that the stresses in its structure are 15 % lower than those in the typical one. A feature of the findings is that the proposed improvement of the container helps improve its strength in operation by reducing the loads acting on it. The scope of practical use of the results is the engineering industry, namely, railroad transport. At the same time, the conditions for the practical application of the research results are the introduction of energy-absorbing material as a component of the sandwich panel. This study will contribute to devising recommendations for designing modern structures of vehicles of a modular type and for improving the efficiency of the transport industry